The effect of r-salbutamol on apparent digestibility, feed efficiency, growth, carcass characteristics, and meat quality of feedlot lambs - De Klerk, Martin Johannes (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.